2014
DOI: 10.1097/01.nt.0000453844.83969.21
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers and Inflammation

Abstract: such as barbecue and spicy foods such as chili, tacos, and crab cakes. Health professionals, researchers, and policymakers have an opportunity to work together at the interface of food science and nutrition to help translate the science of spices and herbs into improved consumer eating patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…We showed that CG exerted antioxidant effects against intestinal mucositis by increasing GSH levels and decreasing MDA levels in the duodenum of mice subjected to 5-FU-induced intestinal mucositis. This finding is in agreement with the result of a previous study demonstrating that CG formulations exerted an antioxidant effect by decreasing MDA levels [47].…”
Section: Discussionsupporting
confidence: 93%
“…We showed that CG exerted antioxidant effects against intestinal mucositis by increasing GSH levels and decreasing MDA levels in the duodenum of mice subjected to 5-FU-induced intestinal mucositis. This finding is in agreement with the result of a previous study demonstrating that CG formulations exerted an antioxidant effect by decreasing MDA levels [47].…”
Section: Discussionsupporting
confidence: 93%